2016
DOI: 10.1080/23723505.2017.1318200
|View full text |Cite
|
Sign up to set email alerts
|

Systematic pathological component scores for skin-containing vascularized composite allografts

Abstract: Here we report a systematic scoring system developed from MHC-mismatched porcine skin-containing VCA. Biopsies from 20 VCA, 9 autologous skin flaps and 9 normal skin were analyzed to optimize the methodology and set thresholds. The components quantified were: perivascular cells/dermal vessel (pc), perivascular dermal infiltrate area (pa), luminal leukocytes/capillary or venule (c), epidermal infiltrate (ei), epidermal apoptosis or necrosis (e), endarteritis (v), and chronic allograft vasculopathy (cav). To eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…A second pathologist further assessed the skin xenotransplants for cellular infiltrations and other microscopic indicators of immunological rejection via two methods 42 . The Banff Classification for skin‐containing composite tissue allograft pathology was used to categorize xenotransplant rejection.…”
Section: Resultsmentioning
confidence: 99%
“…A second pathologist further assessed the skin xenotransplants for cellular infiltrations and other microscopic indicators of immunological rejection via two methods 42 . The Banff Classification for skin‐containing composite tissue allograft pathology was used to categorize xenotransplant rejection.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Etra et al proposed a modified Banff grading system for AR in a swine VCA model, which suggests that the extent of inflammatory infiltrate in the epidermis and dermal inflammation are significant factors in grading of AR in a swine VCA model 11 . Additionally, Rosales et al proposed a component AR scoring system in porcine VCA models that includes perivascular cells/dermal vessel, perivascular dermal infiltrate area, capillaritis (luminal leucocytes/capillary or venule), epidermal infiltrate, epidermal injury and necrosis, endarteritis, and chronic allograft vasculopathy, and suggested that the proposed scoring system might be clinically relevant, due to similarity of human and porcine skin 12 …”
Section: Discussionmentioning
confidence: 99%
“…endarteritis, and chronic allograft vasculopathy, and suggested that the proposed scoring system might be clinically relevant, due to similarity of human and porcine skin. 12 Despite the existence of the Banff 2007 Working Classification of Skin-CTA Pathology, there is yet no standardized classification system for CR in VCA; however, the literature does include descriptions of CR features in some animal and human VCA models. 13,14 During the Banff 2007 meeting that resulted in the above-mentioned classification system, it was proposed that sclerosis, atrophy, loss of adnexa, nail loss, cutaneous ulceration, and ischemic changes or necrosis are clinical presentations of CR.…”
Section: Early Chronic Rejectionmentioning
confidence: 99%
“…Vascular injury is not included within the current Banff system but has been recognized in both experimental and clinical specimens at the higher rejection grades [44][45][46]. Similarly, the current grading system and the majority of the literature focus on features of acute cellular rejection, and relatively, little work has focused on antibody-mediated rejection (AMR), not least due to the scarcity with which it has been diagnosed and the absence of a clear correlation between C4d deposition and donor-specific antibody (DSA) formation in VCA [12,47,48].…”
Section: Acute Rejection In Vascularized Composite Allograftsmentioning
confidence: 99%
“…There is no assessment of vascular inflammation, or features of chronic allograft vasculopathy, both of which could yield insights into variations in the pattern and pathogenesis of rejection. Indeed, the benefits of a systematic approach to the assessment of VCA histopathology have been acknowledged at recent international workshops, and collaborative efforts to develop systematic scoring systems, akin to those in routine use for assessment of renal transplant biopsies, for instance, are ongoing [45,65].…”
Section: Clinical Grading Of Vca Rejectionmentioning
confidence: 99%